DATA MINING UNTUK ESTIMASI JUMLAH SIDANG PERKARA NARKOTIKA DI PANCUR BATU MENGGUNAKAN METODE REGRESI LINIER BERGANDA STUDI KASUS CABANG KEJAKSAAN NEGERI DELI SERDANG DI PANCUR BATU - Wira Apriani (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Narcotics in Indonesia especially in the surrounding terrain makes calculating the number of Narcotics users very difficult to do manually. Based on these problems, this research was conducted using data mining modeled with multiple linear regression that aims to estimate the number of Narcotics users. Data mining can be done for estimation by using a complete record that provides the value of the target variable as a predictive value. Estimation of the state (ups and downs) of the dependent variable (criterion), if two or more independent variables as predictor factors are manipulated (increased in value) is the Multiple Linear Regression method. In the process. Multiple Linear Regression illustrates the change in the value of the number of Narcotics cases (Y) caused by changes in the number of Narcotics cases not yet resolved (X1) when the number of Narcotics cases has dropped (X2) is constant, and vice versa. The system is applied showing the range of Y values derived from the sample is 79 - 61 = 18 (maximum value - minimum value), while the standardized side estimate is 1.105887, so it can be concluded that the Multiple Linear Regression method is accurate to be used as a predictor of the number the Narcotics case trial at the Deli Serdang District Attorney's Office in Pancur Batu can accurately be used with the Multiple Linear Regression method.